Supervision of the Use of School Operational Assistance (BOS) Funds in State Special Schools (SLB) in South Jakarta City, DKI Jakarta Province - Daniyyah Damar Fitriyanti; R. Luki Karunia; Bambang Giyatno (Neo Journal of economy and social humanities, 2025)
The purpose of this study is to analyze the implementation of BOS fund management supervision at SLB Negeri in South Jakarta Administrative City, identify factors that influence the implementation of BOS fund management supervision at SLB Negeri in South Jakarta Administrative City and find out the strategy for BOS fund management supervision at SLB Negeri in South Jakarta Administrative City. The method used in this study is a qualitative research method. The data analysis techniques used in this study are data collection, data reduction, data presentation, and drawing conclusions. The results of this study are that BOS fund supervision at SLB DKI Jakarta Province has been carried out systematically through standard stages, evaluation, comparison, and correction based on the latest regulations and digital reporting. Supervision is supported by education and transparency, but is constrained by the limited number of supervisors, time constraints, and competency gaps. The supervision strategy is carried out through a coaching and sanction approach. In general, supervision has been running well but it needs strengthening of human resources, coordination, and optimization of technology to be more effective and have a maximum impact on improving the quality of special education.